Microbiology Learning Based on Bioentrepreneurship: Prospective Teacher’s Perception - Muliadi, Agus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
This study aims to explore prospective teacher’s perception towards microbiology learning on bioentrepreneurship. The study is a descriptive-exploratory research with 56 respondents of prospective teacher of biology at Mandalika University of Education. The instrument used was questionnaire with Guttman scale and it was valitaded (expert validation). The data was analyzed by using descriptive and inferential statistics of Analysis of Variance (ANOVA). The result of prospective teachers’ perception  show that (1) the second semester are 70,00% with good enough, the forth semester are 70,00% with good enough, the sixth semester are 93,75% with very good, while the eighth semester are 92,00% with very good categories; (2) the Analysis of Variance with significant of 0.000 was lowest than alpha values (<0,05). This study can be concluded that there is significant differences of prospective teacher’s perception towards microbiology learning on bioentrepreneurship